2015
DOI: 10.1097/prs.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intersyringe Processing on Adipose Tissue and Its Cellular Components

Abstract: The mechanical procedure of shuffling lipoaspirated fat does not alter its tissue viability or its microscopic structure. The absence of impact on the stromal vascular fraction in the assessed parameters suggests that shuffling can be executed according to surgical needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 22 publications
3
35
0
1
Order By: Relevance
“…Isolation with the AIS was the longest intraoperative isolation procedure (SundarRaj et al ., ). Shuffling lipoaspirate 5 or 30 times through a luer‐to‐luer lock syringe will take 5 or 30 s, respectively, and were therefore the fastest procedures (Osinga et al ., ). In general, the tested nonenzymatic procedures take less time than the enzymatic procedures (Table , B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation with the AIS was the longest intraoperative isolation procedure (SundarRaj et al ., ). Shuffling lipoaspirate 5 or 30 times through a luer‐to‐luer lock syringe will take 5 or 30 s, respectively, and were therefore the fastest procedures (Osinga et al ., ). In general, the tested nonenzymatic procedures take less time than the enzymatic procedures (Table , B).…”
Section: Resultsmentioning
confidence: 99%
“…Osinga et al . (), reported that most of the adipocytes remain intact after shuffling five or even 30 times. Consequently, the effect of shuffling only cannot be stated as an isolation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…24 The key variable in their study involved a luer stopcock with a 90-degree bend and an internal diameter of 2 mm which is smaller than our luer fitting (3.76 mm). The combined effect of the lower flow rate and smaller stopcock diameter essentially cancel each other out with respect to Re (Equation 1), so we would still expect laminar flow if the samples had similar viscosities.…”
Section: Discussionmentioning
confidence: 97%
“…This technique results in mechanically refined adipose tissue that can be freely injected through smaller cannulas and syringes. 24 Similarly, nanofat processing is an extreme version of this that has been demonstrated effective for the correction of superficial rhytides and pigmentation. 13 While both techniques appear to be safe and effective, little is known with regards to the effect these various techniques have on the different components of the tissue and its cellular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation